Room-temperature synthesis of nanometric and luminescent silver-MOFs - Celis-Arias, Vanessa; Garduño-Wilchis, Ismael A.; Alarcón, Gilberto; González Chávez, Fernando; Garrido Guerrero, Efrain; Beltrán, Hiram I.; Loera-Serna, Sandra (Frontiers in Chemistry, 2023)
Three silver-MOFs were prepared using an optimized, room-temperature methodology starting from AgNO₃ and dicarboxylate ligands in water/ethanol yielding Ag2BDC, Ag2NDC (UAM-1), and Ag2TDC (UAM-2) at 38%–48% (BDC, benzenedicarboxylate; NDC, 1,8-naphthalene-dicarboxylate; TDC, p-terphenyl-4,4″-dicarboxylate). They were characterized by PXRD/FT-IR/TGA/photoluminescence spectroscopy, and the former two by SEM. These materials started decomposing at 330°C, while showing stability. The crystal structure of UAM-1 was determined by PXRD, DFT calculations, and Rietveld refinement. In general, the structure was 3D, with the largest Ag-O bond interlinking 2D layers. The FT-IR spectra revealed 1450 and 1680 bands (cm−1) of asymmetrically stretching aniso-/iso-bidentate -COO in coordination with 2/3-Ag atoms, accompanied by Ag-O bands at 780–740 cm−1, all demonstrating the network formation. XRD and SEM showed nanometric-scale crystals in Ag₂BDC, and UAM-1 developed micrometric single-stranded/agglomerated fibrillar particles of varying nanometric widths. Luminescence spectroscopy showed emission by Ag₂BDC, which was attributed to ligand-to-metal or ligand-to-metal–metal transitions, suggesting energy transfer due to the short distance between adjacent BDC molecules. UAM-1 and UAM-2 did not show luminescence emission attributable to ligand-to-metal transition; rather, they presented only UV emission. The stabilities of Ag₂BDC and UAM-1 were evaluated in PBS/DMEM/DMEM+FBS media by XRD, which showed that they lost their crystallinity, resulting in AgCl due to soft–soft (Pearson’s principle) affinity.